Serum TNF-α and biomarkers Levels after Tenofovir in Patients with serum HBeAg-Positive Chronic Hepatitis B : Serum TNF-α and biomarkers and Chronic Hepatitis B - Lai, Xijie (Journal of Medical Biochemistry, 2025)
Introduction: chronic hepatitis B (CHB) is a serious and common infectious disease, the pathogenesis of which has not been fully elucidated. Tenofovir Amibufenamide belongs to the nucleoside reverse transcriptase inhibitor class and was allowed for CHB treatment. This work investigated the effectiveness and safety of Tenofovir Amibufenamide in treating HBeAg-positive CHB. Materials and Methods: 60 patients with HBeAg-positive CHB were grouped: an entecavir (ETV) group (entecavir, 0.5 mg) and a TMF group (Tenofovir Amibufenamide, 0.25 mg) at a 1:1 ratio. Changes in renal function, liver function, and tumor necrosis factor α (TNF-α) levels after 2 years of treatment were analyzed to assess the antiviral efficacy and safety. Results: patients in TMF group showed smaller changes in serum creatinine (Scr) and glomerular filtration rate (GFR) after treatment, and decreased alanine aminotransferase (ALT) and total bilirubin (TBIL), demonstrating obvious differences with those in ETV group (P
Keywords: Serum, TNF-α, serum HBeAg-positive; chronic hepatitis B; Tenofovir Amibufenamide; liver function; renal function